Pengaruh Strategi Critical Incident Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Kelas X IPA SMA Swasta Universitas Islam Sumatera Utara Tahun Pelajaran 2020/2021 Medan Kota - Husaini, Ahmad (Fakultas Agama Islam, 2020)
Critical incident (important experience), a strategy to activate students since the start of learning, students must remember and describe their past experiences in accordance with the topic of the material presented